Novel peripherally and non-peripherally 6-oxyflavone substituted metal-free, zinc(II) and cobalt(II) phthalocyanines: Electrochemical and in situ spectroelectrochemical properties - (:unkn) unknown (WORLD SCI PUBL CO INC, 2018)
In this study, novel tetrasubstituted zinc(II), cobalt(II) and metal free phthalocyanines containing 6-hydroxyflavonoxy moieties at peripheral and non-peripheral positions have been prepared. The phthalonitriles were synthesized from 6-hydroxyflavone with 4-nitrophthalonitrile and 3-nitrophthalonitrile in dimethylformamide. Preparation of tetra-substituted peripheral and non-peripheral metallo-and metal-free phthalocyanines was performed at 170-180 degrees C using the corresponding phthalonitriles in the presence of N,N-dimethylethanolamine, metal acetate and lithium acetate, respectively. The structures of the newly-synthesized phthalocyanine compounds have been characterized by elemental analysis and UV-vis, FT-IR, H-1 NMR and MALDI-TOF mass spectroscopies. Electron transfer properties of the phthalocyanine compounds were investigated by voltammetric and in situ spectroelectrochemical measurements on Pt in dimethylsulfoxide/tetrabutylammonium perchlorate. Zinc(II) and metal-free compounds show Pc ring-based one-electron redox processes, whereas cobalt(II) produces both Pc ring-and metal-based one-electron redox processes, associated with net color changes.
Keywords: phthalocyanine; flavone; electrochemistry; spectroelectrochemistry; INDIUM(III) PHTHALOCYANINES; PHOTOCHEMICAL PROPERTIES; PHOTODYNAMIC THERAPY; COMPLEXES; INHIBITORS; ISOFLAVONOIDS; OXIDATION; CO(II)